A Distinct Subset of Highly Proliferative and Lentiviral Vector (LV)-Transducible NK Cells Define a Readily Engineered Subset for Adoptive Cellular Therapy - Bari, Rafijul; Granzin, Markus; Tsang, Kam Sze; Roy, Andre; Krueger, Winfried; Orentas, Rimas; Schneider, Dina; Pfeifer, Rita; Moeker, Nina; Verhoeyen, Els; Dropulic, Boro; Leung, Wing (Frontiers in Immunology, 2019)
Genetic engineering is an important tool for redirecting the function of various types of immune cells and their use for therapeutic purpose. Although NK cells have many beneficial therapeutic features, genetic engineering of immune cells for targeted therapy focuses mostly on T cells. One of the major obstacles for NK cell immunotherapy is the lack of an efficient method for gene transfer. Lentiviral vectors have been proven to be a safe tool for genetic engineering, however lentiviral transduction is inefficient for NK cells. We show in this study that lentiviral vector pseudotyped with a modified baboon envelope glycoprotein can transduce NK cells 20-fold or higher in comparison to VSV-G pseudotyped lentiviral vector. When we investigated the mechanism of transduction, we found that activated NK cells expressed baboon envelop receptor ASCT-2. Further analysis revealed that only a subset of NK cells could be expanded and transduced with an expression profile of NK56bright, CD16dim, TRAILhigh and CX3CR1neg. Using CD19-CAR, we could show that CD19 redirected NK cells efficiently and specifically kill cell lines expressing CD19. Taken together, result from this study will be important for future genetic modification and redirecting of NK cell function for therapeutic purpose.